The Team Leader Model: an alternative to preceptorship - Russell, K.; Hobson, A.; Watts, Robin (Australian Nursing Federation, 2011)
Objective: To improve the clinical practice environment for student nurses through an increased understanding of the relationships and of the situations in which that practice occurs. Setting: Fremantle Hospital and Health Service (FHHS) in partnership with Curtin University of Technology. Subjects: This project sought to assess a new model of supervision and support based on a team approach, the team being a Registered Nurse, Graduate Nurse and a Student Nurse, that supported students, graduates and staff. Main outcome measures: To determine if the students clinical placement provided a reality of practice, where the student became the leader of the shift, supervised by the supervisor. To understand the relationships of support between graduate and student nurses, and to determine if the allocation of students via the Team Leader method reduced preceptor burnout. Results: The Team Leader Model demonstrated that it provided an improved allocation model of student supervisors, students felt a greater sense of reality of practice, and graduates appreciated the support of the Team Leader. Conclusion: The model has been perceived by staff and students as a practice that can provide for a better clinical practice placement for the student.